Promoting Learning Development as an Academic Discipline - Peter Samuels (Association for Learning Development in Higher Education (ALDinHE), 2013)
Over the past 10 years, Learning Development has become an established practice in many UK universities. Whilst this practice is generally understood and valued by students, its associated epistemology and community of practice is generally not perceived as an academic discipline in its own right by other academics, managers or policy makers. Recently, there has been a move within the Learning Development community to address the challenge of enabling it to discover its Ã¢â¬Ëvoice' as a discipline within the conversation of disciplines. In addition, the current economic climate makes it desirable for the Learning Development community to organise and promote itself as a research-informed discipline so that its professional practice will not be over-embedded or absorbed within faculties to the detriment of students.